Turning Donepezil into a Multi-Target-Directed Ligand through a Merging Strategy - Perone, Rosaria; Albertini, Claudia; Uliassi, Elisa; Di Pietri, Flaminia; de Sena Murteira Pinheiro, Pedro; Petralla, Sabrina; Rizzardi, Nicola; Fato, Romana; Pulkrábková, Lenka; Soukup, Ondrej; Tramarin, Anna; Bartolini, Manuela; et al. (ChemMedChem, 2021)
Thanks to the widespread use and safety profile of donepezil (1) in the treatment of Alzheimer's disease (AD), one of the most widely adopted multi-target-directed ligand (MTDL) design strategies is to modify its molecular structure by linking a second fragment carrying an additional AD-relevant biological property. Herein, supported by a proposed combination therapy of 1 and the quinone drug idebenone, we rationally designed novel 1-based MTDLs targeting Aβ and oxidative pathways. By exploiting a bioisosteric replacement of the indanone core of 1 with a 1,4-naphthoquinone, we ended up with a series of highly merged derivatives, in principle devoid of the "physicochemical challenge" typical of large hybrid-based MTDLs. A preliminary investigation of their multi-target profile identified 9, which showed a potent and selective butyrylcholinesterase inhibitory activity, together with antioxidant and antiaggregating properties. In addition, it displayed a promising drug-like profile.
Keywords: oxidační stres; Blood-Brain Barrier; Cholinesterase Inhibitors; antioxidancia; viabilita buněk; proteinové agregáty; neuroprotektivní látky; ligandy; Cell Line, Tumor; Protein Aggregates; Structure-Activity Relationship; racionální návrh léčiv; Ligands; Alzheimerova nemoc; Alzheimer Disease; Cell Survival; Indans; Neuroprotective Agents; amyloidní beta-protein; acetylcholinesterasa; vztahy mezi strukturou a aktivitou; donepezil; Donepezil; lidé; Antioxidants; Amyloid beta-Peptides; Humans; indany; Drug Design; nádorové buněčné linie; Oxidative Stress; Acetylcholinesterase; cholinesterasové inhibitory; hematoencefalická bariéra